Transformational Leadership and Organizational Communication as Predictors of Employee Performance at the National Library Librarian Development Center - Rafifah, Nida; Akil; Ismail, Achmad Taufik (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2026)
This study aims to analyze the influence of transformational leadership and organizational communication on employee performance within the Librarian Development Center of the National Library of the Republic of Indonesia (Pusbinawan Perpusnas RI) Salemba, Jakarta. This research is motivated by the limited empirical study of the relationship between the two variables in service-based public organizations and the development of national librarians. In addition, previous research has placed organizational communication more as a mediating variable, rather than as an independent variable analyzed with transformational leadership in influencing employee performance. The research uses a quantitative approach with a survey method. The research population amounted to 42 employees and all of them were made respondents through total sampling techniques. Data collection was carried out through questionnaires, observations, and documentation. The research instrument consisted of 36 statement items measured using a five-level Likert scale. Data analysis was carried out through validity, reliability, classical assumption test, multiple linear regression, t-test, F test, and determination coefficient (R²). The results of the study show that transformational leadership and organizational communication have a positive and significant effect on employee performance, both partially and simultaneously. Organizational communication is the variable that has the most dominant influence on improving employee performance. A determination coefficient value of 0.814 indicates that 81.4% of employee performance variations can be explained by transformational leadership and organizational communication. This research confirms that the effectiveness of leadership and internal communication is a strategic factor in improving employee performance in modern public organizations.